The advanced sensing systems for NOₓ based on metal-organic frameworks: applications and future opportunities - Kumar, Pawan (2022)
NOx is one of the most important air pollutants as it can sensitively reflect the air quality in various routes (e.g., as the precursor of acid rain or photochemical formation of ozone (O3)). Among diverse classes of hybrid porous materials, metal-organic frameworks (MOFs) have drawn great attention for various applications including sensing, adsorption, catalysis, energy/gas storage, drug-delivery, and non-linear optics. Such enhanced applicabilities of MOFs are often ascribed to their intriguing features (e.g., their framework architecture, topology, optical properties, and electroluminescent properties). In this review, we initially described the synthesis methodology of MOFs and then covered their uses for NOx sensing applications, especially based on optical and electrochemical principles to address analytical performance, and merits/demerits along with the future opportunities and challenges to this application. To conclude, we discuss the future research directions for this emerging avenue of MOF-based sensing technology.